1988
DOI: 10.1111/j.1464-410x.1988.tb04367.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antisperm Antibodies on Human Sperm Function

Abstract: Antisperm antibodies have been found in about 8% of men with infertility and in 60 to 80% of patients following vasectomy. In order to investigate the way antibodies influence sperm function we studied serum and seminal plasma from patients with infertility (n = 61) or undergoing vasovasostomy (n = 25). These antisera were characterised to determine their TAT titre, the nature of the target antigens and their capacity to interfere directly with fertilisation. The results indicate that antibodies from both grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 25 publications
2
22
1
Order By: Relevance
“…Meinertz et al [9] also stressed the finding that especially the occur rence of IgA in the seminal fluid was associated with low conception rates. Aitken et al [10] described the capacity of antibodies to stimulate or suppress sperm/oocyte fu sion. In vasovasostomized patients they saw a higher stimulating effect on this fusion than in patients with pri mary infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Meinertz et al [9] also stressed the finding that especially the occur rence of IgA in the seminal fluid was associated with low conception rates. Aitken et al [10] described the capacity of antibodies to stimulate or suppress sperm/oocyte fu sion. In vasovasostomized patients they saw a higher stimulating effect on this fusion than in patients with pri mary infertility.…”
Section: Discussionmentioning
confidence: 99%
“…In fact either inhibition (133)(134)(135), or enhancement (136), both inhibition and enhancement (106,137), or no effect were found (138,139). Some discrepancies may be explained by procedural differences.…”
Section: The Hamster Egg Penetration Test (Hept) As Model Of Studymentioning
confidence: 99%
“…Some discrepancies may be explained by procedural differences. Generally, when inhibitory effects were reported, donor sperm were exposed to ASA after capacitation or directly into the insemination medium: in any case, free antibodies were not removed before sperm/oocytes coincubation (106,134,135). Using this procedure, an interaction of ASA with internal sperm antigens, which can be revealed after the acrosomal loss, has been supposed to explain the inhibitory effect (140).…”
Section: The Hamster Egg Penetration Test (Hept) As Model Of Studymentioning
confidence: 99%
“…Finally, the demonstration of the actual responsibility of ASA in impairing cervical mucus penetration has been provided by matching donor sperm suspensions exposed to sera containing ASA against the same sperm suspensions exposed to control sera without ASA (106).…”
Section: Interference With Cervical Mucus Penetrationmentioning
confidence: 99%
“…With this assumption, the study of clinical infertility due to ASA, regarded as "experiments of nature" in fertility reduction, has been approached to identify candidate sperm antigens for immunocontraceptive development (193,194). Numerous investigators have reported the identification of specific antigens using sera from WHO reference bank or from independent collections (106,(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206). However, characterization of sperm antigens was limited to SDS-Page in most studies, and results varied widely due to the methods and reagents employed.…”
Section: Perspectivementioning
confidence: 99%